Causal Association of Coffee Consumption and Total, Knee, Hip and Self-Reported Osteoarthritis: A Mendelian Randomization Study - Zhang, Yangchang; Fan, Jun; Chen, Li; Xiong, Yang; Wu, Tingting; Shen, Shisi; Wang, Xu; Meng, Xuchen; Lu, Yanjun; Lei, Xun (Frontiers in Endocrinology, 2021)
Background: The causal association between coffee consumption and the risk of OA is limited. This study was conducted to identify the potential causal effects of coffee consumption on total, knee, hip, and self-reported OA. Methods: Genome-wide association studies (GWAS) of OA were derived from the UK Biobank, comprising 50,508 participants of European ancestry (10,083 with cases and 40,425 controls), and genetic data for specific diagnosed knee OA (4462 cases and 17,885 controls), hip OA (12,625 cases and 50,898 controls), and self-reported OA (12,658 cases and 50,898 controls). Primary and secondary genetic instruments (11 SNPs and 8 SNPs) were selected as instrumental variants from GWAS among 375,833 and 91,462 participants. Two-sample Mendelian randomization (MR) analyses were performed to test the effects of the selected single nucleotide polymorphisms (SNPs) and the OA risk. The causal effects were primarily estimated using weighted median and inverse-variance weighted method with several sensitivity analyses. Results: The MR analyses suggested that coffee consumption were associated with an increased risk of overall OA (OR:1.009, 95% CI:1.003-1.016), knee OA (OR:1.023, 95% CI:1.009-1.038), self-reported OA (OR:1.007, 95% CI:1.003-1.011), but not hip OA (OR: 1.012, 95%CI:0.999-1.024) using primary genetic instruments. Similar results were found when using secondary genetic instruments. Additionally, the sensitivity analyses for leave-one-out methods supported a robust association between exposure traits and OA. Conclusion: Our findings indicate that coffee consumption exerts a causal effect on total, knee, and self-reported OA risk, but not at the hip. Further research is required to unravel the role of coffee consumption in OA prevention.